Comparison Between Hyperbaric Bupivacaine with and Without Fentanyl in Reducing Visceral Pain During Cesarean Delivery Under Spinal Anaesthesia: - Thapa, Rashmi; Pooja Paudyal, Pooja; Pradhan , Bishwas; Koirala, Megha; Parajuli, Bashu Dev (Journal of Nepal Health Research Council, 2025)
Background: Visceral pain occurred during cesarean delivery during spinal anesthesia can be decreased with a higher dose of bupivacaine. However, larger doses of bupivacaine increases the risk of high sensory block. We hypothesized that addition of fentanyl to bupivacaine intrathecally could intensifies the sensory block and improves the quality of intraoperative analgesia. The aim of this study is to compare incidence of visceral pain between hyperbaric bupivacaine with or without fentanyl during cesarean delivery under spinal anesthesia.Methods: In this prospective randomized controlled trial, 72 term parturient with ASA PS II undergoing cesarean delivery under spinal anesthesia were randomly distributed into two groups. Group B received 2.2ml (11mg) of 0.5% hyperbaric bupivacaine while Group BF received 2 ml (10mg) of 0.5% hyperbaric bupivacaine and 0.2ml (10µg) of fentanyl intrathecally. Incidence of intraoperative visceral pain, maternal hemodynamics, side effects and APGAR score were compared.Results: During exteriorization of uterus, 11% of parturient in Group BF and 44% parturient in Group B complained of intraoperative visceral pain with significant difference between two group (p=0.002). The intraoperative rescue analgesia was given in 22 % parturient in Group BF and 33% parturient in Group B (p= 0.29). Maternal vital parameters like blood pressure, heart rate, oxygen saturation and respiratory rate were comparable between two groups. APGAR score was similar in both groups.Conclusion: Addition of intrathecal fentanyl to hyperbaric bupivacaine was effective in reducing intraoperative visceral pain during cesarean delivery with stable maternal hemodynamics and without neonatal side effects. Keywords: Bupivacaine; cesarean delivery; fentanyl; spinal anesthesia; visceral pain